A Comparative Study for Adsorptive Removal of Remazol Red R and Remazol Black B from Aqueous Solution by ZnO (Dhaka University Journal of Science, 2018)
Adsorptive removal of remazol red R (RRR) and remazol black B (RBB) from aqueous solution has been investigated by using ZnO as an adsorbent. Time for adsorption equilibrium, kinetics of adsorption at different initial concentrations of dyes and adsorption isotherms at different temperatures have been studied. Adsorption capacity increased with increasing initial dye concentration. The pseudo first-order and pseudo second-order kinetics were used to describe kinetic data and the rate constants were evaluated. Experimental data fits better in the pseudo second-order kinetic model than in the pseudo first-order kinetic model for both the dyes. Langmuir and Freundlich isotherm models were applied to describe the adsorption of RRR and RBB onto ZnO powders. Langmuir isotherm model provided a better correlation for the experimental data in comparison to the Freundlich isotherm model. Adsorption of both RRR and RBB on ZnO are physical in nature and increases with decreasing temperature. The equilibrium adsorption capacity decreases from 3.43 mg/g at 200C to 2.36 mg/g at 400C for RRR whereas that in the case of RBB changes from 0.77 mg/g at 300C to 0.75 mg/g at 400C. Adsorption of RRR on ZnO was found to be three times higher than the adsorption of RBB at a particular temperature. A model for adsorption of both the dyes has been proposed.Dhaka Univ. J. Sci. 66(2): 121-127, 2018 (July)